ANALOGI DALAM PENGAJARAN FISIKA - Apit Fathurohman (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
In physics, there are abstract and concrete concepts. Abstract concept of physics can make trouble for student in identifying concepts of physics except if attributed to everyday experience. Bridging problems of abstract concept can be done by using a model of learning are called analogies. Analogies are often used as explanatory devices in the classroom. All Analogies make a comparison between a target concept (the concept you are aiming to have students understand) and the analog concept. Analogies can engender alternative conceptions because some students visualize the analog in a different manner than the teacher and/or invalid analog-target transfers are left unchallenged. For analogies to be effective, it appears essential that the analogy be familiar to as many students as possible, that shared attributes be precisely identified by the teacher and/or students, and that the unshared attributes should be explicitly identified. This paper is description about an implementing Teaching With Analogies (TWA) model in physics instructional at senior high school